Green synthesis of tetraketones: crystal structure, DFT studies and Hirshfeld surface analysis of 2, 2′-((3, 4-dimethoxyphenyl) methylene) bis(3-hydroxy-5, 5-dimethylcyclohex2-enone). (29th January 2021) - Shashi, R.; Begum, Noor Shahina; Panday, Anoop Kumar
Abstract: The present work deals with a practically efficient protocol designed for the synthesis of tetraketones using ultrasound in the presence of boric acid as the catalyst. One of the tetraketone, (3a ) was confirmed by crystallographic studies. The molecules in crystal lattice are held together by weak intermolecular C–H···O, C–H··· π and intramolecular O–H···O interactions. Hirshfeld surface analysis was carried out for the graphical visualization, while, the 2D fingerprint plots provide percentage contribution of each individual atom-to-atom interactions. Finally, to determine molecular electrical transport properties, we studied the energy difference between highest occupied, HOMO, and lowest unoccupied, LUMO orbitals.